Oceanographic Factors on Coastal Aggregation of Reef Manta (Mobula alfredi) in The Manta Sandy, Raja Ampat, Indonesia - Awaludin Ahsin; Retno Hartati; Widianingsih Widianingsih; Erlangga D. Sitorus; Hidayati Azizah; Hadi Endrawati (Marine Science Department Diponegoro University, 2022)
Reef Manta rays (Mobula alfredi) is an iconic species and under the IUCN Red List of Threatened Species it is classified as vulnerable. Although the decline of population has been reported due to their very high demand and economic value especially for their dried gill plates, they are present all year round at Manta Sandy, Dampier Strait, Raja Ampat, Indonesia. The appearance of M. alfredi may affected by environmental factors. Therefore, this study was aimed to determine the sighted frequency of M. alfredi and their related environmental factors during east and west monsoon. Underwater Visual Census (UVC) and camera trap (PhotoID) method were used to observe the appearance of M. alfredi. The remotely oceanographic data, such as sea surface temperature, chlorophyll-a, sea surface current and tidal data, in the same M. alfredi observation time were obtained from the web of www.oceancolor.gsfc.nasa.gov, www.Hycom.org, Geospatial Information Agency (GIA) and then analyzed using Seadas, Excel, and ArcMap (Geographic Information System). The results showed that during the west monsoon M. alfredi appeared more often (174 sighting) than in the east monsoon (5 sighting). Those appearances were connected with slightly warmer sea surface temperature and high value phytoplankton which is related to zooplankton. For planktivorous elasmobranch, lower sea surface current and high tidal value affect the distribution of zooplankton in those area, so give high feeding opportunity for M. alfredi. High sighted M. alfredi during west monsoon in Manta Sandy attract tourists, therefore regulation for their conservation need to be implemented.